Performance of a powdered activated carbon (PAC) augmented activated sludge process treating semi-aerobic leachate - Aghamohammadi, N.; Aziz, H.A.; Isa, M.H.; Zinatizadeh, A.A.; Nasrollahzadeh, H.S.; Ghafari, S. (2007)
Semi-aerobic leachate is characterized by organic matter (COD, BOD) which is relatively low in concentration and difficult to biodegrade. In conventional treatment systems, the low biodegradability is attributed to partial stabilization of leachate at the landfill. Biological treatment of leachate in Malaysia is not well established and any important data for the treatment process is not available. The behavior of microbes is unknown for semi aerobic leachate. This research was conducted to establish some of the important data in the biological treatment of semi-aerobic leachate with and without the influence of powdered activated carbon (PAC). For the present study, semi aerobic leachate was collected from Pulau Burung Landfill Site (PBLS), Nibong Tebal, Penang, Malaysia. The experiment involved operating two 16 L laboratory-scale activated sludge reactors in parallel at room temperature and adjusted to pH of 6.5±0.5. One of the reactors was supplemented with powdered activated carbon (PAC) of 75-150 μm size to observe its effect on leachate biodegradation. The results showed enhanced reactor performance due to PAC addition COD, NH4-N, NO3-N, TKN, BOD and colour removals was higher.